Managemen Pengelolaan Alat dan Bahan di Laboratorium Mikrobiologi - Indra Gunawan (UPT Laboratorium Terpadu, Universitas Diponegoro, 2019)
Laboratory is one of the important facilities in the teaching and learning process, as a place to study or as a source of learning, laboratories must have a comfortable and safe nature. A laboratory that is comfortable means that the needs or needs to carry out activities are available in the appropriate place or are easily accessible if used and used. Whereas laboratories that are safe means that all storage of hazardous materials and dangerous activities has been prepared and anticipated. Laboratory management will run more effectively if the laboratory structure is supported by elements including the head / head of the laboratory, practicum coordinator, Education Laboratory/ Technician / Laboran / Analyst staff and laboratory staffThe purpose of laboratory management is to create an atmosphere of microbiology laboratories, especially those that are comfortable and safe for users which include students, researchers and visitors to the laboratory and staff who manage the laboratory. The method used is quantitative based on literature studies (metaanalisis). Framework for meta-analysis concepts based on the determination of layout and space, management of tools and materials, order and laboratory safetyIt is expected that the implementation of good management in the laboratory will create a safe and comfortable laboratory atmosphere. Based on the results above, it can be concluded that there is a relationship between management and good governance with a safe and comfortable atmosphere for users and laboratory managers.